Bioeconomy and Global Inequalities Socio-Ecological Perspectives on Biomass Sourcing and Production - Backhouse, Maria; Lehmann, Rosa; Lorenzen, Kristina; Lühmann, Malte; Puder, Janina; Rodríguez, Fabricio; Tittor, Anne (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access book explores bioeconomy and bioenergy policies across South America, Asia and Europe. It discusses how a transition away from a fossil and towards a bio-based economic order alters, reinforces and challenges socio-ecological inequalities. A series of conceptual discussions and case studies with a multidisciplinary background in the social sciences illuminate how the deployment of biomass sources from the agricultural and forestry sectors affect societal changes concerning knowledge production, land and labour relations, political participation and international trade. How can a global perspective on socio-ecological inequalities contribute to a critical understanding of bioeconomy? Who participates in the negotiation of specific bioeconomy policies and who does not? To what extent does the bioeconomy affect existing socio-ecological inequalities in rural areas? What are the implications of the bioeconomy for existing relations of extraction and inequalities acrossregions? The volume is an invitation to reflect upon these questions and more, at a time when the need for an ecological and socially just transition away from a carbon intensive economy is becoming increasingly pressing. The editors, Maria Backhouse, Rosa Lehmann, Kristina Lorenzen, Malte Lühmann, Janina Puder, Fabricio Rodríguez and Anne Tittor are all social scientists and members of the Junior Research Group "Bioeconomy and Inequalities. Transnational Entanglements and Interdependencies in the Bioenergy Sector" funded by the German Federal Ministry of Education and Research (BMBF).